Application and Characterization of Blueberry Fruit Pigment as the Photosensitizer for High Performance and Stable Natural Dye Sensitized Solid Solar Cells - Malikaramge, A.; Nagarajan, P.; Rjapakse, G; Kumara, A.; Velauthapillai, Dhayalan; Ravirajan, P. (University of Jaffna, 2019)
The natural dye pigment of blueberry was extracted from its peals using our own acetonitrile assisted method and used in a liquid electrolyte free natural dye sensitized solid solar cell (NDSSSC) which exhibited he highest efficiency (ɳ) of 1.7% and short circuit current density (Jsc = 11 mA/cm2) for the blueberry dye sensitized any type of solar cell. Natural dyes are always inexpensive, nontoxic and reliable sources that can be used in photovoltaic application as a cheap alternative for commercial expensive synthetic dyes. The typical problems of stability of natural pigments and the unreliability, expensiveness and the toxicity of the iodide / tri-iodide electrolyte were addressed by introducing a deposition of p-CuI on dye incorporated nanoporous TiO2 films from a solution containing a crystal growth inhibitor Triethylammine Hydrothiocyanate (THT) by drop casting method in order to make a NDSSSC. I-V characteristics and impedance measurements were carried out to investigate the photovoltaic performance and further characterized by UV-Visible spectroscopy, FTIR spectroscopy and SEM. Stability measurements were carried out for a period of 30 days and promisingly showed a good stability
Keywords: Natural dye; DSSC; Blueberry dye; solid cells; Copper Iodide